Increased leg muscle strength and power after 6 weeks of trapping exercise in male college students - Bayu Akbar; Hari Setijono; Oce Wiriawan; Muhammad Wahyono; Achmad Nuryadi; Septyaningrum Putri Purwoto; Adi Pranoto (Universidad de Murcia, 2024)
The aim of this study was to determine the effect of trapping exercise for 6 weeks on leg muscle strength and power in male college students. This was a quasi-experimental study with a research design of one-group pre-test/post-test design. The sample amounted to 11 male students. Trapping exercise were carried out for 6 weeks with a frequency of 3-times exercise per week. A back and leg dynamometer was used to measure strength and the Accupower was used to measure power. Strength and power were measured before and after the 6-week trapping training. Paired samples t test was used to compare pre-test and post-test. The results showed that there was a significant increase in the average strength between pre-test vs. post-test (104.50±18.10 vs. 114.40±20.60 kg, p=0.000). Likewise, the mean power between pre-test vs. post-test (636.20±58.30 vs 656.60±64.00 Joules, p=0.000). The conclusion was that trapping exercise for 6 weeks with a frequency of 3-times exercise per week increased strength and power in male college students.